Incidental Vocabulary Learning in Second Language Acquisition: A Literature Review - Falcon Dario Restrepo Ramos (Universidad Nacional de Colombia, 2015)
This literature review aims to analyze previous studies that address the incidental learning of vocabulary in second language acquisition. The articles included in this literature review look into the understanding of vocabulary learning through incidental means, the relationship of reading and incidental vocabulary learning, and the strategies and tasks that promote the incidental learning of vocabulary. The findings show that L2 learners develop much of their vocabulary by incidental means through exposure to words in informative contexts. Moreover, this exposure is promoted by reading, and enhanced through multimodal glosses. Further research may focus on listening for higher lexical retention rates, the circumstances that allow incidental learning of multi-word phrases and collocations, and the use of technology-based methods for incidental vocabulary acquisition.